2022
DOI: 10.3389/fbioe.2022.974460
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of iturin A by strengthening fatty acid synthesis modules in Bacillus amyloliquefaciens

Abstract: Iturin A is a biosurfactant with various applications, and its low synthesis capability limits its production and application development. Fatty acids play a critical role in cellular metabolism and target product syntheses, and the relationship between fatty acid supplies and iturin A synthesis is unclear. In this study, we attempted to increase iturin A production via strengthening fatty acid synthesis pathways in Bacillus amyloliquefaciens. First, acetyl-CoA carboxylase AccAD and ACP S-malonyltransferase fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Plasmid pHY300PLK was applied for gene overexpression strain construction, and construction procedure of gene ycxA overexpression strain was served as an example (Gao et al 2022 ). Briefly, promoter P bacA (Genebank ID 16053260), gene ycxA (14,767,903), and amyL terminator (16,055,532) were amplified and fused by SOE-PCR; the fusion fragment was inserted into pHY300PLK at Eco RI/ Sac I sites; and diagnostic PCR and DNA sequence confirmed that YcxA overexpression vector pHY-YcxA was successfully constructed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid pHY300PLK was applied for gene overexpression strain construction, and construction procedure of gene ycxA overexpression strain was served as an example (Gao et al 2022 ). Briefly, promoter P bacA (Genebank ID 16053260), gene ycxA (14,767,903), and amyL terminator (16,055,532) were amplified and fused by SOE-PCR; the fusion fragment was inserted into pHY300PLK at Eco RI/ Sac I sites; and diagnostic PCR and DNA sequence confirmed that YcxA overexpression vector pHY-YcxA was successfully constructed.…”
Section: Methodsmentioning
confidence: 99%
“…As for iturin A, the promoter of iturin A synthase operon was replaced by promoter P bacA in B. amyloliquefaciens HZ-12, which led to 1.3-fold increases of iturin A yield in the previous work of our group (Xu et al 2020 ). Meanwhile, strengthening fatty acid synthesis via overexpression of acetyl-CoA carboxylase AccAD, ACP S-malonyltransferase FabD, soluble acyl ACP thioesterase TesA, and long-chain fatty acid-CoA ligase LcfA benefited iturin A synthesis, which yield was increased to 2.96 g/L by 2.95-fold (Gao et al 2022 ). Although various works have been done for efficient synthesis of iturin A, its yield (2 ~ 4 g/L) was still significantly lower than that of surfactin (> 10 g/L) (Table S1 ), which limits iturin A application development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactin synthesis was accomplished by non-ribosomal peptide synthetase (NRPSs), which mainly involves three steps: the synthesis of fatty acid chain, the activation and loading of fatty acids, and the extension of the peptide chain [51]. Fatty acid synthesis plays as a critical role in lipopeptide synthesis and the gene expression levels are positively correlated with the lipopeptide yield [52,53]. Previous studies have proved that strengthening branched-chain fatty acid biosynthetic pathways was an e cient approach to enhance lipopeptide yield [54].…”
Section: Metabolic Pathways and Regulatory Mechanisms Response For Sp...mentioning
confidence: 99%
“…13 A remarkable 6.59-fold increase in iturin A yield was attained through enhanced fatty acid supply. 14 The suppression of the spoIIIE gene, which is involved in the development of spores and biofilms, led to a 37% enhancement in the production of fengycin. 15 Increased expression of the yngH gene, which encodes for biotin carboxylase II, improves the production of fatty acids and increases surfactin yield by 43%.…”
Section: Introductionmentioning
confidence: 99%